Eleição de áreas prioritárias para pagamento por serviços ambientais: Uma análise em nível de microbacia - Rosa, Fernando Salles; Tonello, Kelly Cristina; Lourenço, Roberto Wagner [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2016)
In this study, we selected priority areas for conservation of water resources to support programs for environmental services (PSA) payment. The proposal will be used for the implementation of the PSA pilot project in the watershed of the Murundu, Ibiúna-SP, to support PSA public policy to foster sustainability. To do so, land use information layers, vegetative cover and slope were organized in a GIS environment in order to allow through cross tabulation the selection of priorities to generate a thematic map. From this map, we performed qualitative and a quantitative analysis, as well as priority setting ranges. The tools used have shown to be useful in supporting decision-making and research and public policy in PSA, focusing on increasing the governance of water resources. It is clear that remuneration for “standing forest definitely represents the major prospect in the watershed of the river’s Murundu, as well as the possibility of converting monetary values of the payment into other forms of support to providers of the service according to their priorities.
Selection of priority areas for payment of environmental services: An analysis at the watershed level
Keywords: Public policy; Recipient-provider; Springs